2009
DOI: 10.1016/j.apal.2009.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Model-theoretic complexity of automatic structures

Abstract: a b s t r a c tWe study the complexity of automatic structures via well-established concepts from both logic and model theory, including ordinal heights (of well-founded relations), Scott ranks of structures, and Cantor-Bendixson ranks (of trees). We prove the following results: (1) The ordinal height of any automatic well-founded partial order is bounded by ω ω . (2) The ordinal heights of automatic well-founded relations are unbounded below ω CK 1 , the first non-computable ordinal. (3) For any computable or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In [20] it is proven that if X is regular and X admits an ordinal α then α < ω ω . Generally, Khoussainov and Minnes [15] showed that if X is FA recognizable and X admits a well-founded partial order A then the height of A is below ω ω . Another nice example is a recent result by Tsankov [29] showing that no regular language admits the structure (Q; +), the additive group of rational numbers.…”
Section: Domain Dependencymentioning
confidence: 99%
“…In [20] it is proven that if X is regular and X admits an ordinal α then α < ω ω . Generally, Khoussainov and Minnes [15] showed that if X is FA recognizable and X admits a well-founded partial order A then the height of A is below ω ω . Another nice example is a recent result by Tsankov [29] showing that no regular language admits the structure (Q; +), the additive group of rational numbers.…”
Section: Domain Dependencymentioning
confidence: 99%
“…In [24] it is proven that if X is regular and X admits an ordinal α then α < ω ω . Generally, Delhommé [6] showed that if X is regular and X admits a well-founded partial order A then the height of A is below ω ω (see also [13]). Also, as mentioned above, Delhommé [6] shows that no regular tree language admits ordinals greater or equal to ω ω ω .…”
Section: Definitionmentioning
confidence: 99%
“…In contrast to these positive results, Khoussainov, Nies, and Rubin have shown that the isomorphism problem for automatic graphs is Σ 1 1 -complete [17]. Results on the model theoretic complexity of automatic structures can be found in [15].…”
Section: Introductionmentioning
confidence: 99%
“…The proof idea is to transform a recursive successor tree into an automatic one by adding the computation (i.e., sequence of transitions) that verifies the edge (u, v) as a path between the nodes u and v; a similar idea was used in [20,15].…”
Section: Theoremmentioning
confidence: 99%
See 1 more Smart Citation